Critical review of the diifferent perspectives on the relationship between the general and absolute in five religions - Morteza Chitsazian; Mahdi Narimanpour (مطالعات تطبیقی فقه و اصول مذاهب)
The relationship of the general and absolute is one of the issues that there is a lot of disagreement among the Scholars of Islamic jurisprudence. they agree unanimously that the general implies assignationally inclusion; But in relation to absolute assignated there is different opinions. Sunni and shia scholars believe that the absolute is due to the assignation; but the later Shia scholars recognize that the term is not the case. The former is becoming two groups. Some scholars have introduced the absolute assigned an indefinite word in the manner of proof and others have introduced it a quiddity without a condition and they who do not consider it due to assignation believe that the term indicate nature; Without an absolute be a restriction to an assignated, But they have disagreed on the role of the basics of wisdom. The famous opinion believes that the role of the basics of wisdom is to obtain restrictions, but the Imam and his subjects believe that the role of the basics of wisdom is to eliminate restrictions. From these views, it seems that the Imam's view that expresses: absolute indicates natures and that's the reason for removing the basics of wisdom is more justified